Pengaruh Kepemimpinan, Kompetensi dan Mutasi Jabatan terhadap Kinerja Dispora Kabupaten Berau dengan Kualitas Perencanaan sebagai Variabel Intervening - Herman Herman; Arif Jauhar Tontowi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of leadership, competence, and job rotation on the performance of the Youth and Sports Office (Dispora) of Berau Regency with planning quality as an intervening variable. The phenomenon of frequent job rotation in local government raises questions about organizational performance effectiveness. This research uses a quantitative approach with an explanatory research design. The research population consists of all employees of Berau Regency Dispora, totaling 87 people, with a sample of 72 respondents using the purposive sampling technique. Data collection used a questionnaire with a 5-point Likert scale that had been tested for validity and reliability. Data analysis used Structural Equation Modeling (SEM) with AMOS 24.0 software. The results indicate that leadership has a significant positive effect on planning quality (β=0.342, p<0.05), competence has a significant positive effect on planning quality (β=0.389, p<0.05), but job rotation has a significant negative effect on planning quality (β=-0.273, p<0.05). Planning quality is proven to have a significant positive effect on organizational performance (β=0.654, p<0.01). Planning quality mediates the influence of leadership and competence on performance but does not mediate the influence of job rotation on performance. This research contributes to the development of public sector human resource management theory and provides policy recommendations for optimizing local government organizational performance.